A STUDY ON ROLE OF GOVERNMENT IN FOSTERING UNORGANIZED WORKERS - Gangadhara. K; Dr. Meghavath Govind Naik (EPRA International Journal of Environmental Economics, Commerce and Educational Management (ECEM), 2023)
The present study deals with analysis the role of government in fostering unorganized workers .The main objective of the study is to find out the problems faced by the unorganized labours in their working place and the central and state government schemes for the labours especially unorganised workers. The study is based on secondary date collected from the various websites, journals, articles newspapers etc..The Government played an important role in fostering unorganized workers.